2019
DOI: 10.1371/journal.pone.0226874
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine profile of the VCD-induced perimenopausal model rat

Abstract: During the transition to menopause, women experience a variety of physical and psychological symptoms that are directly or indirectly linked to changes in hormone secretion. Establishing animal models with intact ovaries is essential for understanding these interactions and finding new therapeutic targets. In this study, we assessed the endocrine profile, as well as the estrous cycle, in the 4-vinylcyclohexene diepoxide (VCD)-induced follicular depletion rat model in 10-day intervals over 1 month to accurately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 70 publications
(110 reference statements)
7
30
0
Order By: Relevance
“…In a recently published article, Carolino and colleagues studied the endocrine profile of POI rats induced by VCD. They reported that the FSH levels in POI rats did not significantly change for at least 90 days after the VCD administration [50]. In another study, VCD did not influence the FSH levels until 240 days from the start of the experiment [24], and Mayer and colleagues reported that VCD injection to mice do not significantly increase the FSH levels until 37 days [27].…”
Section: Discussionmentioning
confidence: 97%
“…In a recently published article, Carolino and colleagues studied the endocrine profile of POI rats induced by VCD. They reported that the FSH levels in POI rats did not significantly change for at least 90 days after the VCD administration [50]. In another study, VCD did not influence the FSH levels until 240 days from the start of the experiment [24], and Mayer and colleagues reported that VCD injection to mice do not significantly increase the FSH levels until 37 days [27].…”
Section: Discussionmentioning
confidence: 97%
“…Perimenopause is the transition period from the reproductive to the nonreproductive stage of life, with important changes in their hormone, including FSH and estrogen [ 12 ]. Women may experience a number of symptoms associated with the menopausal transition, including vasomotor symptoms, vaginal dryness, sleeping disorders, and the onset of depression [ 13 ], and menopause transition was also associated with adverse health indicators, such as increased TC and LDL-C levels, increased cardiovascular risk and a greater bone loss/increased bone turnover [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…women have a typical hormonal profile, with reduction in progesterone plasma concentrations while estradiol concentrations are normal or erratically high (Santoro et al, 1996;Prior and Hitchcock, 2011). The same pattern was observed in rats submitted to chronic VCD injections (Reis et al, 2014;Pestana-Oliveira et al, 2018;Carolino et al, 2019). Therefore, we consider this an effective way to assess whether perimenopause was induced in female rats.…”
Section: Measurement Of Estradiol and Progesterone Plasma Concentrations Most Perimenopausementioning
confidence: 64%
“…Note: The collection of the vaginal smear and evaluation of the estrous cycle must be carried out in the early morning, between 7:30 and 9:30 am to prevent the cells present in the vaginal fluid from moving from one phase to the next. Since until close to 90 days after the onset of VCD treatment the proportion of rats that cycle regularly (about 20%) is the same in control rats and those treated with VCD (Carolino et al, 2019). Only control and VCD treated rats cycling regularly be used in the experiments performed before 90 days after starting VCD injections.…”
Section: Pellets Implantation Surgerymentioning
confidence: 99%
See 1 more Smart Citation